Сучасні підходи до тестування та якості програмного забезпечення - Дем’яненко, М. С. (ХНУРЕ, 2024)
In the contemporary tech environment, the critical role of software testing cannot be overstated. Its core purpose is to evaluate and enhance software quality, ensuring functionality, security, and ultimately user satisfaction, which in turn builds customer trust. The emergence of Artificial Intelligence (AI) in software development heralds a new era, significantly boosting the efficiency and effectiveness of these processes. The integration of AI innovates the various phases of software testing, markedly improving the testing methodology and leading to the creation of superior software products.
Keywords: якість програмного забезпечення; software